(untitled) (Research, Society and Development, 2021)
The scale of involvement with work has been reported as a significant predictor of various outcomes in the workplace. However, there is limited empirical evidence about the instrument with an association of behavioral results. Therefore, the objective of this study was to evaluate the factor structure of the involvement with the work of workers in different work situations. 504 Brazilian workers participating in organizations or in teleworking participated in the study. After analyzing the data, it was observed that the factorial structure of the scale measure is consistent and proved to be invariable when evaluating it in the samples with the specific work situation. Thus revealing consistent psychometric indicators, confirmed by the analysis of the t test. Thus, such results enable the development of psychosocial intervention practices when it is intended to invest in the development and behavioral and emotional maintenance of workers both in the initiation and in the maintenance of work actions.